Feasibility and Efficacy of His Bundle Pacing or Left Bundle Pacing Combined With Atrioventricular Node Ablation in Patients With Persistent Atrial Fibrillation and Implantable Cardioverter‐Defibrillator Therapy. Issue 24 (17th December 2019) - Wang, Songjie; Wu, Shengjie; Xu, Lei; Xiao, Fangyi; Whinnett, Zachary I.; Vijayaraman, Pugazhendhi; Su, Lan; Huang, Weijian
Abstract : Background: Persistent atrial fibrillation may lead to a higher probability of inappropriate shocks in heart failure patients with an implantable cardioverter‐defibrillator (ICD). The aim of this study was to evaluate the impact of His‐Purkinje conduction system pacing combined with atrioventricular node ablation in improving heart function and preventing inappropriate shock therapy in these patients. Methods and Results: A total of 86 consecutive patients with persistent atrial fibrillation and heart failure who had indications for ICD implantation were enrolled from January 2010 to March 2018. His‐Purkinje conduction system pacing with ICD and atrioventricular node ablation was attempted in 55 patients, and the remaining patients underwent ICD implantation only. Left ventricular (LV) ejection fraction, LV end‐systolic volume, New York Heart Association (NYHA) classification, shock therapies, and drug therapy were assessed during follow‐up. Overall, 31 patients received ICD implantation with optimal drug therapy (group 1). atrioventricular node ablation combined with His‐Purkinje conduction system pacing was successfully achieved in 52 patients (group 2). During follow‐up, patients in group 2 had lower incidence of inappropriate shock (15.6% versus 0%, P <0.01) and adverse events ( P =0.011). Meanwhile, improvement in LV ejection fraction and reduction in LV end‐systolic volume were significantly higher in group 2 than in group 1 (15% versus 3%, P <0.001; and 40 versus 2 mL, P <0.01, respectively). NYHA functional class improved in both groups from a baseline 2.57±0.68 to 1.73±0.74 in group 1 and 2.73±0.59 to 1.42±0.53 in group 2 ( P <0.01). Conclusions: His‐Purkinje conduction system pacing combined with atrioventricular node ablation is feasible and safe with a high success rate in persistent atrial fibrillation patients with heart failure and ICD indication. It can significantly reduce the incidence of inappropriate shocks and improve LV function.